Strategy Analysis UKM of Government Policy in Implementing Restrictions of Community Activities (PPKM) to Handle the Covid-19 Pandemic - Zaenuddin Imam (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
During the COVID-19 pandemic that hit Indonesia, it caused a recession in various sectors. Related sectors include the SME sector. In many businesses, the number of buyers is down and profits are falling. This is because of government regulations regarding people at home. Therefore, you need to develop a strategy to keep them alive and increase resale. The survey method used is qualitative analysis with exploratory steps with participant observation techniques. Researchers used qualitative methods. Qualitative Research Methods is research that can be carried out through direct contact, understanding the opinions of open-minded people and understanding through symbolic interactionism researchers conducted research in Jember. The results of this study reveal various strategies that can be applied by entrepreneurs, including selling online, digital marketing, improving product and service quality, building relationships, and building relationships with customers. It is hoped that the results of the research can be carried out by economic actors, who take into account changing circumstances and economic actors will be able to survive.